(untitled) (Memorandum: Memória e História em Psicologia, 2024)
Margaret Archer tackles the concept of human person within the framework of the vexata quaestio of the relations between individual and society. To sum up the problem: is it society (social forms and institutions) that make the human person or does the person make society? This issue has gripped all of social theory since the beginning of modernity. In past decades, the debate divided scholars between those inclined to forefront the person’s free agency and those who instead gave first place to the constraints of social structures; the two solutions could be mixed, but the outcome was always somewhat hazy. The solution Archer offers is that neither answer is correct, nor is any mixture of the two, because these mixtures do not allow us to understand how action and structure are entangled. The challenge is to understand how and why there is this entanglement, or rather link, which preserves the autonomy of both the person (her freedom) and the social structures (their conditioning power), without confusing the two.